MiR-195-5p regulates cell proliferation, apoptosis, and invasion of thyroid cancer by targeting telomerase reverse transcriptase. Issue 1 (1st January 2021) - Liu, Zhiwen; Zhang, Li; Chen, Wen; Yuan, Fenqian; Yang, Zhi; Liu, Sheng; Le, Fei
ABSTRACT: In most human primary cancers, the expression, or telomerase activity, of telomerase reverse transcriptase ( TERT ) is detectable. However, the mechanism of TERT activity within oncogenesis of thyroid cancer remains largely unknown. In this study, we identified miR-195-5p as having involvement in cell proliferation, apoptosis, and invasion in human thyroid cancer. MTT was used to measure cell proliferation, Transwell chamber was used to measure invasion. Western blotting was used to detect the expressions of TERT, PCNA, and Ki67. Target gene prediction software predicted that TERT may be the target gene of miR-195-5p. Luciferase reporting system was used to identify the targeting relationship. A significant increase of in TERT expression was observed by immunohistochemistry compared with normal tissue, however, a decrease in miR-195-5p expression using qRT-PCRand western blot compared with normal cells. Functional analysis demonstrates that miR-195-5p negatively correlated with TERT and inhibited TERT expression through its interaction with the TERT 3ʹ-untranslatedregion (3ʹ-UTR). Overexpression of miR-195-5p was shown to inhibit proliferation and invasion, and promote apoptosis of CAL-62 thyroid cancer cells. miR-195-5p-mediatedeffects were rescued by the overexpression of TERT . Altogether, our data demonstrate that miR-195-5p regulates cell proliferation, apoptosis, and invasion in human thyroid cancer via TERT, providing evidence of a new potential therapeutic target for further investigation.